Performance Evaluation of User Selection Protocols in Random Networks with Energy Harvesting and Hardware Impairments - Tan Nhat Nguyen; Tran Trung Duy; Phuong Thanh Tran; Miroslav Voznak (Advances in Electrical and Electronic Engineering, 2016)
In this paper, we evaluate performances of various user selection protocols under impact of hardware impairments. In the considered protocols, a Base Station (BS) selects one of available Users (US) to serve, while the remaining USs harvest the energy from the Radio Frequency (RF) transmitted by the BS. We assume that all of the US randomly appear around the BS. In the Random Selection Protocol (RAN), the BS randomly selects a US to transmit the data. In the second proposed protocol, named Minimum Distance Protocol (MIND), the US that is nearest to the BS will be chosen. In the Optimal Selection Protocol (OPT), the US providing the highest channel gain between itself and the BS will be served. For performance evaluation, we derive exact and asymptotic closed-form expressions of average Outage Probability (OP) over Rayleigh fading channels. We also consider average harvested energy per a US. Finally, Monte-Carlo simulations are then performed to verify the theoretical results.